S62798, a TAFIa inhibitor, accelerates endogenous thrombolysis in a murine model of pulmonary thromboembolism. (25th November 2020) - Sansilvestri-Morel, P; Bertin, F; Lapret, I; Neau, B; Blanc-Guillemaud, V; Petit-Dop, F; Tupinon-Mathieu, I; Delerive, P
Abstract: : Pulmonary embolism (PE) is the third leading cause of cardiovascular death in western countries. The enhancement of fibrinolysis constitutes a promising approach to treat thrombotic diseases. In patients, venous thrombosis and thromboembolism risks are associated with increased plasma levels of TAFI (Thrombin Activatable Fibrinolysis Inhibitor) antigen as well as the active form TAFIa. S62798 is a competitive, selective and potent human TAFIa inhibitor (IC50±SD=11.2±0.4nM). It is however less potent on mouse TAFIa (IC50±SD=270±39nM). Here, we tested the ability of S62798 to enhance endogenous fibrinolysis in a mouse model of pulmonary thromboembolism. Human Tissue Factor (TF) was injected in C57Bl6 male mice. Ten minutes later, mice (n=4 to 14 per group) were treated (IV) with S62798 (from 0.01 to 100mg/kg) or vehicle (0.9% NaCl). Ten or twenty minutes (min) later, mice were anesthetized and lungs were collected, homogenized and pulmonary fibrin was quantified by ELISA. Results are expressed as ratio of geometric mean of pulmonary fibrin (μg/mL): tested treatment/ vehicle [95% confidence interval (CI)]. Ten minutes after S62798 treatment, pulmonary fibrin deposition was dose-dependently decreased with a Minimal Effective Dose of 0.04mg/kg [90% prediction interval 0.037 - 0.051] and an ED50 of 0.03mg/kg [95% CI: 0.01; 0.06]. Mice were then treated with 0.1mg/kg S62798 or vehicle (10 min after TF induction) and fibrin deposition in lungs was quantified 10 and 20 minutes post S62798 treatment. The level of pulmonary fibrin deposition was significantly decreased (p<0.0001) compared to vehicle group (ratio 0.31 [0.21; 0.45] at 10 min; 0.35 [0.24; 0.51] at 20 min). Finally, the effect of S62798 (1mg/kg) in combination with heparin was evaluated (n=10/group). When administered 10 min before TF injection, heparin (2000IU/kg) significantly (p<0.0001) decreased pulmonary fibrin level (20 min post TF: ratio 0.03 [0.01; 0.05]). When treatment was done in a curative setting (10 min post TF), heparin alone had no effect (p=0.85) on fibrin deposition (ratio 0.96 [0.65; 1.43]) whereas a similar significant (p<0.0001) decreased pulmonary fibrin deposition was observed in response to S62798 alone or associated with heparin (ratio 0.27 [0.18; 0.40] (S62798 alone) and 0.29 [0.20; 0.43] (S62798+heparin)). In this model, curative S62798 treatment, alone or associated to heparin, accelerated clot degradation by potentiating endogenous fibrinolysis and thus decreased pulmonary fibrin deposition. Due to its capacity to enhance endogenous fibrinolysis, S62798, which has completed phase I studies, is expected to be a therapeutic option for intermediate high risk PE patients on top of anticoagulants. With early recanalization, S62798 should rapidly reduce pulmonary artery pressure and resistance, with concomitant improvement in right ventricular function, preserving cardiac function, and reducing acute PE-related morbidity and mortality in these patients. Funding Acknowledgement: Type of funding source: None